An Ethnic Press In Malaysia: A Study Of Sin Chew Daily 2012-2013 - Ng, Miew Luan (2019)
The Malaysian Chinese ethnic press Sin Chew Daily (SCD) plays the role of serving and bridging the Chinese community with the government and other social groups in the setting of a multi-ethnic nation. In a larger context of media, society, the state and the market, the role of SCD could also be examined from the perspective of the desired media’s roles in a democratic society. It is in this setting that this study aims to examine the representation of SCD on the Chinese cultural preservation agenda, nation-building, the ruling and opposition parties, and human rights issues before the 13th General Elections (GE13). The research methods used included content analysis, in-depth interview and discourse analysis. Ten news themes were identified based on the research objectives and the news reports, editorials and opinion columns in the ‘Opinion Corner’ that were published between May 1, 2012 and April 30, 2013 in the national edition of SCD and were analyzed based on the headlines, page numbers, source of news, news slants/tones and pictures used. The analysis of the editorials and the opinion columns has excluded the page numbers and pictures used due to ‘Opinion Corner’ was published at the same location and no pictures were used. Six respondents, mainly the media gatekeeper, leaders of the ruling and opposition political parties, an intellect and the NGOs representatives were interviewed. In order to understand the ideology of SCD, a total of nine editorials/leaders were selected for discourse analysis. The content analysis of the news reports and opinion columns indicated that SCD gave the most coverage on political parties and political issues before the GE 13.